Hubungan Fungsi Eksekutif dengan Bullying Victimization pada Siswa SMPN X di Lima Puluh Kota - Erfi Amanda; Maya Yasmin (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Bullying victimization remains a significant issue in educational environments, including at SMPN. This phenomenon has a detrimental impact on the victims, both physically and psychologically. Bullying victimization refers to the experience of an individual being subjected to aggressive actions by others repeatedly over time, with the intent to cause harm or discomfort. These actions can be carried out by one or more individuals and often affect the victim's well-being in the long term. One of the factors believed to influence bullying victimization is executive function. Executive function refers to a person’s ability to control impulses, plan, make decisions, and adjust behavior to achieve long-term goals. This function plays a crucial role in regulating responses to social and emotional situations, which can affect whether an individual is more vulnerable to becoming a victim of bullying. This study aims to examine the relationship between executive function and bullying victimization among 194 students at SMPN X Lima Puluh Kota. The research uses a quantitative correlational approach with proportionate stratified random sampling. The instrument used to measure bullying victimization was developed based on the aspects defined by Smith, et al. (1999), while the executive function instrument was based on the aspects outlined by Spinella (2005). The results of the analysis using the product moment method show a significant negative correlation between executive function and bullying victimization, with a correlation value of r = -0.863 and p = 0.000 (p < 0.05). This indicates that the better the executive function of students, the lower the level of bullying victimization they experience. Conversely, students with weaker executive functions are more susceptible to becoming victims of bullying.